Предмет: Математика,
автор: Аноним
Помогите пожалуйста
Приложения:
Ответы
Автор ответа:
4
1) (3 см - 1 см) * 2 см + (3 см * 1 см) =
= 2 см * 2 см + 3 см² =
= 4 см² + 3 см² =
= 7 см²
2) 2 см * 3 см + (3 см - 2 см) * 1 см =
= 6 см² + 1 см * 1 см =
= 6 см² + 1 см² =
= 7 см²
3) 3 см * 3 см - (3 см - 2 см) * (3 см - 1 см) =
= 9 см² - 1 см * 2 см =
= 9 см² - 2 см² =
= 7 см²
Похожие вопросы
Предмет: Қазақ тiлi,
автор: kol01
Предмет: Английский язык,
автор: noonto
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: История,
автор: egor435
Предмет: Физика,
автор: maksIgnatov